Effects Of A Computer-Programmed Instructional Strategy On Basic Science Students’ Learning Outcome In Two Instructional Settings In Ondo State, Nigeria - Moriyike LALEYE, Ademiotan (International Journal of Scientific Research and Management (IJSRM), 2019)
This study investigated the effects of computer-based learning on students’ academic performance and the learning setting that yields better when students are exposed to Computer- programmed Instructional Package .This research study tends to find out the efficacy of a Computer Assisted Instructional Package (CAIP) on students’ performance in Basic Science. In actualising these, Quasi-experimental pre-test- post-test research design was used. Two secondary schools were purposively selected and assigned to Experimental groups 1 and 2 in equal numbers. Students in Experimental group 1 were exposed to CAIP individually and Experimental group II in Cooperative groups. An equivalent school was selected as control. 40 students in JSS 3 were randomly selected from each of the schools. Test-retest method was used in finding the reliability of BSAT which was used for collecting data. Result was 0.78 at 0.5 level of significance. Data collected was analysed using descriptive and inferential statistics of percentages and Analysis of Covariance (ANCOVA).  The result of the analysis of co-variance and the Scheffé post hoc revealed that students taught with the developed package performed significantly better than their counterparts taught with conventional method of instruction.It was also discovered that the cooperative group, where a class of forty students are grouped into 10 enhanced better and faster learning than individualised learning. Results from the  instructional settings show that knowledge acquisition was enhanced in all with the cooperative instructional setting performing better than their counterparts in individualised instructional setting and conventional group(individualized=X=66.53, cooperative=X=76.75, conventional=X=59.40). Consequently, the paper recommends that cooperative instructional setting should be encouraged in learning Basic Science.